Perbaikan Sifat Kimia Oxisol dengan Pemberian Bahan Humat dan Pupuk P untuk Meningkatkan Serapan Hara dan Produksi Tanaman Jagung (Zea mays, L.) - Herviyanti Herviyanti; Chici Anche; Gusnidar Gusnidar; Irwan Darfis (Jurnal Solum, 2012)
A research was carried out at glass house and at Soil Laboratory of Faculty of Agriculture, Andalas University Padang. The experiment was aimed to determine the interaction between humic material from compost and P fertilizer on some chemical properties of Oxisol, nutrient uptake and corn production. This experiment consisted of 2 factors (4 x 4) with three replications which were allocated in completely randomized design (CRD). The first factor was humic material having 4 doses (0, 400, 800, and 1200 ppm) and the 2nd factor was P fertilizer having 4 doses (100%, 75%, 50%, and 25% of recomendation (R)). The result showed that there was : 1) Interaction between humic materials and P fertilizer for the quality the corn seeds. Application of 800 ppm humic material improved the quality of the seeds even though at low level of P fertilizer. 2) Then, it also increased availability of P by 23.03 ppm, N total by 0.09 %, and decreased Al-exch by 0.53 me (100 g)-1 and Fe-exch by 25.62 ppm compared to threatment without application of humic material. Likewise, nutrients (N and P) uptake by plant also increased by 0.28 and 0.03 %, respectively. 3) Application of P fertilizer at 75 % R increased soil P availability by 3.77 ppm, N and P content of plant by 0.43 % and 0.06 %, and seed weight by 13.20 g and decreased Fe-exch by 21.16 ppm, compared to 25 % R of P fertilizer.Keywords : humic material, P- fertilizer, nutrient uptake